Chemical resistance of eco-concrete – Experimental approach on Ca-leaching and sulphate attack. (30th October 2019) - Steindl, Florian R.; Baldermann, Andre; Galan, Isabel; Sakoparnig, Marlene; Briendl, Lukas; Dietzel, Martin; Mittermayr, Florian
Highlights: New test setup to investigate sulphate attack and leaching on concrete powders. Attack characterised by dissolution and precipitation reactions. Ettringite and calcite formation in short time frame (7 days). Eco-concretes: Important role of limestone quality due to reactive Al availability. pH and superplasticiser influence ettringite nucleation/precipitation rate. Abstract: The chemical resistance of eco-concrete with high levels (35–65 wt-%) of limestone substitution against Ca-leaching behaviour and sulphate attack was investigated by immersing powdered material in a 10 g L −1 Na2 SO4 solution. Time-resolved hydrochemical characterisation of the reactive solutions was coupled with chemical, structural and mineralogical characterisation of the experimental solid materials to describe and to quantify alteration phenomena like the dissolution of portlandite and AFm-phases, transformation of C-S-H gel and the precipitation of ettringite, calcite and hydrogarnet. Nucleation and crystal growth dynamics of ettringite are controlled by the availability of Ca, reactive Al, solution pH and potentially the amount of clay minerals and/or superplasticiser used in the eco-concrete material. The experimental approach allows revealing competing reaction pathways and kinetics causing concrete damage in sulphate-loaded environments and to tailor eco-concrete towards an elevated degree of chemical resistance.